Fungsi Pengawasan Majelis Pengawas Daerah Terhadap Penegakan Kode Etik Notaris - Yared Hetharie; Merry Tjoanda; Novyta Uktolseja (PAMALI: Pattimura Magister Law Review, 2022)
Introduction: Notaries have a very important role in Indonesia, to serve the community in terms of making an authentic deed as evidence or as a legal requirement for a certain legal action.Purposes of the Research:  Review and analyze the supervision carried out by the Regional Supervisory Council on the Enforcement of the Notary Code of Ethics.Methods of the Research: The research was conducted using a normative juridical method with a c statutory approach, conceptual approach and comparative approach a by specifically analyzing the performance of the institution and its authority in the implementation of law enforcement in the Maluku Sea based on the legislation which was then analyzed qualitatively.Results of the Research: The MPD Supervision function has so far been carried out well but not yet optimal because there are still violations of the code of ethics by a notary. In carrying out the duties and functions as a notary, there are factors that affect the violation of the code of ethics by a notary, namely internal factors and external factors. The Regional Supervisory Council performs the function of supervising notaries by conducting regular inspections of the notary's monthly report, inspection of the notary's office and examination of alleged violations of the code of ethics committed by a notary.